Simulating Free-Space Optical Communications to Support a Li-Fi Access Network in a Smart City Concept - Darusalam, Ucuk; Nathasia, Novi Dian; Zarlis, Muhammad; Priambodo, Purnomo Sidi (CommIT (Communication and Information Technology) Journal, 2024)
Smart city development has grown rapidly in the decades since 4G and 5G technologies have been released. Moreover, a highly reliable network is required to support the Internet of Things (IoT) and mobile access within a city. Light Fidelity (Li-Fi) technology can provide huge bitrate transmission and high-speed communications. In the research, a backbone based on Free-Space Optical (FSO) communication (FSO) is designed through simulation to provide a Li-Fi access network with a high capacity data rate. The originality of the proposed method is the implementation of double filtering techniques, which gives an advantage when forwarding the signal to a node and improves the quality of the signal received by the Li-Fi. The FSO as the Optical Relaying Network (ORN) is designed with a configuration of 12 channels of Dense Wavelength Division Multiplexing (DWDM) amplified by optical amplifiers in the transmitter and receiver. The signal output is filtered by a Fiber Bragg Grating (FBG) and a Gaussian filter. In the simulation, the ORN has node spacing in the range of 500 m to 2,000 m. Then, the data transmission rate at 120 Gbps is provided by the implementation of DWDM channels to serve as an access network. From the simulation, the FSO backbone can optimally deliver highly reliable Li-Fi access networks. When the nodes are spaced in a 500–2,000 m range, the Bit-Error-Rate (BER) performance is produced at the order of 10−6.